The Vela-Puppis open clusters Pismis 8 and Pismis 13 - Giorgi, Edgard Ervar Salvador (2005)
CCD UBVI imaging photometry was carried out in the fields of the open clusters Pismis 8 and Pismis 13, located in the Vela-Puppis region in our Galaxy. MK spectral types have also been determined for a number of stars located in the fields of these two clusters which were used to secure membership among the brightest stars. Since our photometry goes to a fainter limit than previous studies we could provide better reddening, distance and age determinations. Both clusters are located close to the edge of the local arm in the third quadrant. Pismis 8 is a cluster about 5-7 My old located at 2000 pc from the Sun, while Pismis 13 was found at 2750 pc with a probable age of about 100 My. The estimate of the slopes of the mass functions in both cases yielded x ≈ 1.7 and x ≈ 2.1 for Pismis 8 and 13 respectively.